Multimodal biometric system built on the new entropy function for feature extraction and the Refined Scores as a classifier. Issue 7 (1st May 2015) - Mamta; Hanmandlu, Madasu
Highlights A new entropy that can modify the probabilities in the function is formulated. Two information set based features: EGI and EEI are derived from the above function. A unique multimodal biometric system comprising IR face, iris and ear is developed. A classifier based on Refined Scores that use cohort scores in refining is devised. The combined scores from individual modalities are fused at the score level fusion and then improved by RS method.